« Faire un tri dans le monde des applis » - Esteban Bopp; Johnny Douvinet; Damien Serre (Netcom)
The smartphone applications intended to inform and alert the population in case of major risks might strongly reduce the communication time between the decision centers and users located in a potentially damaging environment. However, there are many applications in France, and this lies in a competitive process between the providers and a confusion among future users. Thus, is it possible to reduce such an offer, and if we want to keep only the best solutions (i.e. that have the highest alert and information potential), on which criteria can we classify them? In order to answer to these objectives, this study proposes an evaluation protocol based on various indicators, which take into account the capacity of the applications to send a targeted alert, their attractiveness, the ability of individuals to emit information and number of hazards considered. Results obtained on 50 applications deployed in France show that most of them do no achieve the objectives of the alert, in the sense defined by civil security, due to a single-hazard approach, a unique sense of communication, and a low participation of the smartphone users. The best appli are not also those than have been applied at local scales.